Transcultural language, native Chilean peoples and a new AI-based artistic-cultural expression: Creating a new expression driven by intelligent technologies - Garcia-Lara, Luis F.; Bugueno-Cordova, Ignacio G. (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This work aims to rescue, transcribe and create new artistic and cultural expressions through the use of native peoples’ historical visual recordings, integrating intelligent technologies. For this purpose, a Chilean native peoples’ digital repository is collected, in order to apply a Digital Humanities-based methodology. From the chosen material, portraits are selected, recoloured through a AI-based model; the facial mesh is constructed using a facial landmark detector; the points of the mesh are reconstructed by a Delaunay triangulation; to finally apply an additive manufacturing process. Thus, these physical pieces allow to compare the native people’s own physiognomies, creating new cultural expressions.